Evaluation of a social program in the city of Puno, Peru - Cusicuna, Jose; Neira, Idaluz; Mamani, Javier; Aragón, Walker (Gestionar: revista de empresa y gobierno, 2023)
The objective of this work was to evaluate the filtration, coverage and effectiveness of the social program "Vaso de Leche" in the Provincial Municipality of Puno, Peru. The research followed a quantitative, descriptive, explanatory and non-experimental cross-sectional approach. The unit of analysis was the filtration, coverage and effectiveness of the Glass of Milk Program, while the observation unit was the beneficiary population of the Program. The total population considered was 4,309 beneficiaries and as a result of simple random sampling, 353 beneficiaries were surveyed. It was found that 57.51% of the beneficiaries indicate that the filtering in the Program is fine, 56.94% are in favor of the Program's coverage; as well as 58.36% of the beneficiaries consider that the Program is effective. As a conclusion, it can be affirmed that the program is effective in its criteria for filtering, coverage and attention to the beneficiaries.
Keywords: coverage; effectiveness; evaluation; filtering; social program